Instrument development for understanding factors influencing mammography compliance among Iranian women in Metropolitan Tehran, Iran - Ahmadian, Maryam; Abu Samah, Asnarulkhadi; Emby, Zahid; Redzuan, Ma'rof (Canadian Center of Science and Education, 2010)
Breast cancer is the most widespread cancer among women worldwide. The success of breast cancer screening initiatives depends on the target women and their attitudes. The aim of this study is to develop an instrument for the understanding of women’s socio-psychological factors in relation to mammography screening. The study is exploratory in nature and combines three theories. These theories include the health belief model (HBM), theory of reasoned action (TRA) and the social cognitive theory. The purpose of the inquiry is to examine the behavioural and socio-psychological factors inspiring women participation in mammography screening. A five level Likert scale was employed to discover factors influencing women participation in mammography. Self-administered questionnaire was developed and modified based on previous literatures. A total of 400 women aged 35-69 years, were randomly selected. The study was conducted among female clients of maternity hospitals affiliated to Medical Sciences of Tehran University, Tehran, Iran. Principal Components Analysis was applied to describe the psychometric evaluation of the instruments measuring self efficacy, beliefs, social influence and barriers. Principle axis factorization generated four factors that accounted for 72% in the variance of psychosocial items. The reliability of the data and scale was computed with Cronbach’s Alpha. The values were 0.993, 0.850, 0.709 and 0.952 for self efficacy, beliefs, social influence and barriers respectively. The alpha values exceeded 0.70 suggested as acceptable inter-item reliability threshold, indicating high correlation among the variables in the data set. Consequently, the sets of items yielded results consistent with the complete instrument. However, the current study differed from other studies with respects to the number of factors found. In line with the above, questions that load on each factor and the amount of variance accounted for in each factor should be compared in future studies. Indeed, the findings of the study contributed to the knowledge of the psychometric properties in breast cancer screening instruments, particularly in the utilization of mammography which is needed to asses for other Asian women in future study.